Conceptual Metaphors with the Source Domain of Insanity in English and Serbian - Pavlović Tijana Vesić (Romanian Journal of English Studies, 2016)
The paper explores the conceptual metaphors with the source domain of insanity in English and Serbian, focusing on the features of the source domain that are transferred into target domains. It is shown that the experience that shapes these metaphors relies on the manifestations of mental illness and the common beliefs about mental illness that hold in both languages.